Three-dimensional force and kinematic interactions in V1 skating at high speeds - Stöggl, T.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2014)
To describe the detailed kinetics and kinematics associated with use of the V1 skating technique at high skiing speeds, and to identify factors that predict performance. Methods: 15 elite male cross-country skiers performed an incremental roller-skiing speed test (Vpeak) on a treadmill using the V1 skating technique. Pole and plantar forces and whole-body kinematics were monitored at four submaximal speeds. Results: The propulsive force of the "strong side" pole was greater than that of the "weak side" (P<0.01), but no difference was observed for the legs. The poles generated approximately 44% of the total propulsion, being more effective than the legs in this respect (~59% vs. 11%, P<0.001). Faster skiers exhibited more wellsynchronized poling, more symmetric edging by and forces from the legs, and were more effective in transformation of resultant forces into propulsion. Cycle length was not correlated with either Vpeak or the impulse of total propulsive forces. Conclusions: The present findings provide novel insights into the coordination, kinetics and kinematics of the rm and leg motion by elite athletes while V1 skating at high speeds. The faster skiers exhibit more symmetric leg motion on the "strong" and "weak sides", as well as more synchronized poling. With respect to methods, the pressure insoles and 3D kinematics in combination with the leg push-off model described here can easily be applied to all skating techniques, aiding in the evaluation of skiing techniques and comparison of effectiveness.